(untitled) (Research, Society and Development, 2022)
Objective: to analyze risk factors for neonatal sepsis in a capital of the Brazilian Amazon region. Methods: Retrospective cohort of 411 mothers and their newborns assisted at the municipal maternity hospital from December 2019 to February 2020. Sociodemographic information, history of prenatal care, childbirth type and characteristics of the newborn were collected from the medical records of the binomial mother-child. To estimate the gross and adjusted Relative Risk and 95% confidence intervals, Poisson Robust Regression using Stata®, version 16.0 was used. Result: The incidence of sepsis was 75.42 per 1,000 live births. The risk factors for neonatal sepsis were previous infectious disease (RR: 2.40; 95% CI: 1.21; 4.76), APGAR score less than seven in the first minute (RR: 2.96; 95% CI:1.17; 7.47) and low birth weight (RR: 5.60 CI; 95%: 1.69; 18.50). Conclusion: The identification of predictors for the outcome and early monitoring of pregnant women in prenatal care are important actions to minimize the occurrence of neonatal sepsis. For future studies, it is suggested research in the scope of primary health care and maternity for the qualification of professionals working in the line of care for pregnant women and their families.